Nonuniform transitions of heavy-ion irradiated a-C:H films: Structure and antiwear property degradation analysis. (May 2019) - Xu, Jiao; Duan, Zewen; Qiao, Li; Chai, Liqiang; Chen, Zhang; Guo, Dengji; Wang, Peng; Liu, Weimin
Abstract: A study on hydrogenated amorphous carbon films (a-C:H) was performed to assess the heavy-ion radiation damage and the nature of defects produced by 1.0 MeV Ni ions of fluences varying between 10 14 -10 15 ions/cm 2 . The morphology, chemical and optical structures, and mechanical and tribological properties of the films before and after irradiation were examined. Additionally, the effects of nonuniform structures throughout the films on their antiwear properties were discussed. Studies of the wear tracks have suggested that above the maximum damage depth, film wear rates are mainly related to surface roughness, while after that depth, a rapid failure occurs and wear rates change to be closely related to the irradiation fluence. By making steel pits on irradiated films at varied depths of 0–900 nm, visible/ultra violet Raman diagnostics in the depth direction in the definite penetration depth were achieved, and some striking observations were made that the local sp 3 -to- sp 2 transition in the projected range is approximately 700 nm, accompanied by a bombardment-induced hydrogen release that is most severe on the topmost surface of a-C:H films. It is the combined effects of these two factors that contribute to the rapid failure of irradiated films, particularly at the depth of the projected range. Graphical abstract: Image 1